Candidate Toroidal Electric Dipole Mode in the Spherical Nucleus Ni 58 - Von Neumann-Cosel, P.; Nesterenko, V. O.; Brandherm, I.; Vishnevskiy, P. I.; Reinhard, Paul-Gerhard; Kvasil, J.; Matsubara, H.; Repko, A.; Richter, A.; Scheck, M.; Tamii, A. (Physical Review Letters, 2024)
Dipole toroidal modes appear in many fields of physics. In nuclei, such a mode was predicted more than 50 years ago, but clear experimental evidence was lacking so far. Using a combination of high-resolution inelastic scattering experiments with photons, electrons, and protons, we identify for the first time candidates for toroidal dipole excitations in the nucleus Ni58 and demonstrate that transverse electron scattering form factors represent a relevant experimental observable to prove their nature.
CRIS-Team Scopus Importer:2025-02-04